Pengaruh store image, product signatureness, quality variation, dan quality perception terhadap purchase intention pada produk private brand elektronik - SHERLY SOESANTO; KLEMENS WEDANAJI PRASASTYO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
Abstract : The purpose of this research is to investigate the influence about store image, product signatureness, and quality variation toward quality perception and purchase intention for Carrefour’s electronics of private brand in Jakarta. The method which is used in this research is descriptive and causality. Structural Equation Model was used to established the relationship model of variables, and data analysis for this research is using Maximum Likelihood Estimation method. Sample used for this research was 287 samples that domiciled in Jakarta, have bought electronic product at Carrefour, at least 30 years old, and have income at least Rp 3.000.000. The result of this research is not all of the independent variables are have positive influence toward dependent variables which are quality perception and purchase intention. Store image and product signatureness toward quality perception and product signatureness and quality perception toward purchase intention have positive effect.